Konsep Moderasi Beragama Di Kerajaan Maroko - Fakih Abdul Azis (UIN Mataram, 2020)
This study explains the concept of Islamic Moderation in Morocco. It's an interesting theme for us to observe and study together. Considering that the Moroccan government is one of the successful countries in protecting its territory from the threat of Islamic radicalism groups. Furthermore, the jihadist group launched its attack in Casablanca in 2003. Based on this background, the government, in this matter is King Muhammad VI, considers there is an urgent need to reconstruct Moroccan Islamic moderation. With a view to ensuring the stability of religious, social, cultural and political security in the domestic and regional areas of West Africa. The data was collected through a combination of qualitative studies and field observations of moderation that has been carried out over the past twenty years. The data explains that diversity tolerance has been going on for a long time. Studying King Muhammad VI's decision at His Dhahir al-sharief, the moderation developed by Morocco encompasses several lines. First, by normalizing minority relations represented with the original Moroccan Jews. Second, by building the Institute of Takwin Al-Aimmah in order to bring about the priests of the mosque to have moderate Islamic visions and loving deeply their own homeland.